Developing English teachers' language assessment literacy in an EAP reform context through test design: A case study. (October 2022) - Cui, Yaqiong; Liu, Yunlong; Yu, Hua; Gao, Yuan
Abstract: As the English for Academic Purposes (EAP) reform in China calls for a corresponding reform in assessment to better serve the changing English curriculum, this case study investigates how three EAP teachers' language assessment literacy (LAL) was improved through developing EAP diagnostic tests while engaging themselves in classroom-based assessment and professional development. The scores of teacher-designed EAP writing tests were analyzed through the reliability and validity indexes to show the improvement in the test quality, serving as an indicator of teachers' LAL development. Further evidence of teachers' improved LAL was from student interviews in which students reflected on the effectiveness of EAP instruction and the quality of the teacher-designed EAP tests, and from teacher reflections in which teacher participants reported on their increased confidence in developing classroom-based assessments and designing the diagnostic EAP tests, through nine-month's test-writing practice and participation in professional workshops on assessment. This study presents a case to show how the process of test design, implementation, evaluation, and modification, together with professional workshops and classroom-based assessment, benefits EAP teachers' LAL improvement and professional development.